The Leaf Economics Spectrum Constrains Phenotypic Plasticity Across a Light Gradient - Chen, Xiaoping; Sun, Jun; Wang, Mantang; Lyu, Min; Niklas, Karl J.; Michaletz, Sean T.; Zhong, Quanlin; Cheng, Dongliang (Frontiers in Plant Science, 2020)
The leaf economics spectrum (LES) characterizes multivariate correlations that confine the global diversity of leaf functional traits onto a single axis of variation. Although LES is well established for traits of sun leaves, it is unclear how well LES characterizes the diversity of traits for shade leaves. Here, we evaluate LES using the sun and shade leaves of 75 woody species sampled at the extremes of a within-canopy light gradient in a subtropical forest. Shading significantly decreased the mean values of LMA and the rates of photosynthesis and dark respiration, but had no discernable effect on nitrogen and phosphorus content. Sun and shade leaves manifested the same relationships among Nmass, Pmass, Amass, and Rmass (i.e., the slopes of log–log scaling relations of LES traits did not differ between sun and shade leaves). However, the difference between the scaling constants of shade and sun leaves was correlated with functional trait plasticity. Although the generality of this finding should be evaluated further using larger datasets comprising more phylogenetically diverse taxa and biomes, these findings support a unified LES across shade as well as sun leaves.